2004
DOI: 10.1111/j.1939-1676.2004.tb02614.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Furosemide after Oral Administration to Horses

Abstract: Furosemide is the most common diuretic drug used in horses. Furosemide is routinely administered as IV or IM bolus doses 3-4 times a day. Administration PO is often suggested as an alternative, even though documentation of absorption and efficacy in horses is lacking. This study was carried out in a randomized, crossover design and compared 8-hour urine volume among control horses that received placebo, horses that received furosemide at 1 mg/kg PO, and horses that received furosemide at 1 mg/kg IV. Blood samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 11 publications
3
12
0
Order By: Relevance
“…Frequent IM or IV administration of furosemide can lead to complications such as local infection, perivascular administration of the drug, thrombosis and accidental injection into the carotid artery . A pharmacokinetic and pharmacodynamic study of PO furosemide in healthy horses indicated that the bioavailability of PO furosemide using a single dose of 1 mg/kg was only 5% . In the same study, no differences in urine volume and plasma electrolyte concentrations were noted after PO furosemide administration when compared with control horses.…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…Frequent IM or IV administration of furosemide can lead to complications such as local infection, perivascular administration of the drug, thrombosis and accidental injection into the carotid artery . A pharmacokinetic and pharmacodynamic study of PO furosemide in healthy horses indicated that the bioavailability of PO furosemide using a single dose of 1 mg/kg was only 5% . In the same study, no differences in urine volume and plasma electrolyte concentrations were noted after PO furosemide administration when compared with control horses.…”
Section: Introductionsupporting
confidence: 59%
“…14 A pharmacokinetic and pharmacodynamic study of PO furosemide in healthy horses indicated that the bioavailability of PO furosemide using a single dose of 1 mg/kg was only 5%. 1 In the same study, no differences in urine volume and plasma electrolyte concentrations were noted after PO furosemide administration when compared with control horses.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…(13.31 ± 5.30%), compared to dogs (23.7% [19.9%-28.3%]) and cats (50%) (Benchaoui et al, 2007;Hickman et al, 2008). This finding of reduced bioavailability of orally administered drugs in horses is common and has been found with numerous pharmaceuticals, including furosemide, tramadol, cephalexin, and minocycline (Davis, Salmon, & Papich, 2005;Echeverria, Lascola, Giguere, & Foreman, 2018;Johannson et al, 2004;Shilo et al, 2008). The reasons for this species difference are unknown.…”
Section: Oral F Was Low With High Inter-individual Variability Among mentioning
confidence: 95%